OS REFUGIADOS AMBIENTAIS E O RISCO AO EXERCÍCIO PLENO DA CIDADANIA: UM OLHAR DA FILOSOFIA DO DIREITO (Reflection and Critique Law Magazine, 2020)
This article has as its theme the analysis of the legal treatment of citizenship applied to environmental refugees both in terms of international law and in terms of Brazilian law. As a problem, it exposes the way in which environmental and climatic damages impact the loss of this citizenship from the perspective of Hannah Arendt and Michael Foucault. The article aims to demonstrate in a theoretical way the legal treatment given by the State that has been influencing the full exercise of citizenship of this portion of vulnerable people, using for that purpose a look at the philosophy of law. As methodology, bibliographic and documentary sources were used, the latter translated into legislation dealing with refugee issues and the former with the theoretical assumptions of Arendt and Foucault, associating these elements to the case study of Haitians, victims of the 2010 earthquake. in terms of legal praxis this research brought as a result and conclusion the demonstration that the treatment provided by the Brazilian state to environmental refugees is very far from a fair, dignified and respect for human rights solution and the example of Haiti's environmental refugees reflected in a way this conclusion is clear.